2015
DOI: 10.1111/gcb.13045
|View full text |Cite
|
Sign up to set email alerts
|

Forest tree growth response to hydroclimate variability in the southern Appalachians

Abstract: Climate change will affect tree species growth and distribution; however, under the same climatic conditions species may differ in their response according to site conditions. We evaluated the climate-driven patterns of growth for six dominant deciduous tree species in the southern Appalachians. We categorized species into two functional groups based on their stomatal regulation and xylem architecture: isohydric, diffuse porous and anisohydric, ring porous. We hypothesized that within the same climatic regime:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 99 publications
(139 reference statements)
7
85
1
Order By: Relevance
“…The prediction of forest dynamics and policy-making about forest management and protection are often based on the analysis of radial growth-climate relationships [1,2]. The responses of radial growth to climate varied with the regional variability in moisture conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of forest dynamics and policy-making about forest management and protection are often based on the analysis of radial growth-climate relationships [1,2]. The responses of radial growth to climate varied with the regional variability in moisture conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although climate-growth relationships have been quantified for mature trees of several tropical and temperate species [9,29,68], much remains unknown regarding the sensitivity of tree growth during the early stages of development in semi-arid areas. In this study, we used a generic approach of climate sensitivity assessment that combines field experiments and modelling as an alternative to the traditional dendrochronology technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although trees are central to many climate change adaptation and mitigation strategies, they are vulnerable (particularly in their early growth), to variation in solar radiation, rainfall, and temperature as determinants of potential evapotranspiration (ET 0 ). Changes in these climatic variables, particularly temperature increases and precipitation shortages leading to higher frequencies of extreme weather events (i.e., severe drought and intense rainfall), are expected to affect tree growth and challenge the sustainable management of forests and tree plantations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Elliott et al (2015) analyzed the variability of drought response of six prominent Appalachian hardwood species and observed the individual tree drought-growth relationships varied according to xylem architecture, with diffuse porous species (e.g., yellow-poplar (Liriodendron tulipifera L.), red maple (Acer rubrum L.), sweet birch (Betula lenta L.)) more susceptible to reduced growth than ring-porous oak (Quercus L.) species. Similarly, utilizing US Forest Inventory and Analysis data, Brzostek et al (2014) reported that mesophytic species such as the yellow-poplar and sugar maple (Acer saccharum Marsh.…”
Section: Introductionmentioning
confidence: 99%